Mudança Temporal na Qualidade Vocal após Tireoidectomia - Guimaraes, Michelle Ferreira; Messa, Tamiris Barbosa; Zordan, Lucas Quimquim; Azevedo, Elma Heitmann Mares; Bracet, Margareth Attianezi; Queiroz, Janaína de Alencar Nunes (Distúrbios da Comunicação, 2017)
Lee DY, Lee KJ, Hwang SM, Oh KH, Cho JG, Baek SK, Kwon SY, Woo JS, Jung KY. Analysis of Temporal Change in Voice Quality After Thyroidectomy: Single-institution Prospective Study. J Voice. 2017; 31(2): 195-201.